Analisis kelayakan nasabah sebagai strategi mitigasi risiko kredit pembiayaan murabahah di bprs - hasanah, roudatul (Maliki Interdisciplinary Journal, 2025)
This article discusses Murabahah financing as one of the leading products in Sharia Rural Banks (BPRS) which is in great demand because of its compliance with sharia principles and ease of implementation. However, behind its popularity, this product has a fairly high credit risk if not managed properly. This study aims to analyze the importance of customer feasibility analysis as a credit risk mitigation strategy in murabahah financing in BPRS. The approach used is the 5C + 1S method (Character, Capacity, Capital, Collateral, Condition, and Sharia) as a comprehensive customer feasibility measurement tool. A case study was conducted at BPRS Mitra Mentari Sejahtera which showed that although feasibility analysis had been implemented, the lack of further supervision led to an increase in problematic financing. The results of the study confirm that the implementation of a strong feasibility analysis, supported by a continuous monitoring system and adequate information technology, is essential to maintain the quality of financing and the continuity of BPRS operations.